2004
DOI: 10.1159/000080848
|View full text |Cite
|
Sign up to set email alerts
|

Is the Atopy Patch Test with House Dust Mites Specific for Atopic Dermatitis?

Abstract: Background: The atopy patch test (APT), namely the patch test with aeroallergens, is regarded as specific for patients with atopic dermatitis (AD), but small numbers of positive APT were reported in the past also in atopic subjects without dermatitis and in healthy persons. Objective: The aim of this study was to evaluate the response to the APT with house dust mites (HDM) in subjects nonaffected by AD and to compare the outcomes observed in these cases with those pointed out in AD patients, evaluating also th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 79 publications
2
24
3
Order By: Relevance
“…This statement, supported by the results of some studies, has never been clearly addressed or contradicted by an experiment designed specifically to test it. However, several reports including groups of healthy controls or atopic patients without eczema show a considerable percentage of positive APTs in non‐eczematous patients (19–20). Existing data suggest that the prevalence of positive APTs in children selected for suspected food allergy is higher in those with positive food challenges than in those with negative food challenges (9, 19, 21, 22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This statement, supported by the results of some studies, has never been clearly addressed or contradicted by an experiment designed specifically to test it. However, several reports including groups of healthy controls or atopic patients without eczema show a considerable percentage of positive APTs in non‐eczematous patients (19–20). Existing data suggest that the prevalence of positive APTs in children selected for suspected food allergy is higher in those with positive food challenges than in those with negative food challenges (9, 19, 21, 22).…”
mentioning
confidence: 99%
“…However, several reports including groups of healthy controls or atopic patients without eczema show a considerable percentage of positive APTs in non‐eczematous patients (19–20). Existing data suggest that the prevalence of positive APTs in children selected for suspected food allergy is higher in those with positive food challenges than in those with negative food challenges (9, 19, 21, 22). In general, in healthy or symptomatic subjects, APT results differ widely among tested allergens (naive or standardized food) and depend closely on technical variables (e.g.…”
mentioning
confidence: 99%
“…Using inhalant allergens from two different commercial sources, two sites of application (back and arms), and results in eczematous and healthy subjects retested after two to several weeks, Bygum et al 8 . and Ingordo et al 12 . reported an APT reproducibility of less than 70%, which corresponds to a Cohen's κ value of 0.60–0.85 (satisfactory to highly satisfactory agreement).…”
Section: Discussionmentioning
confidence: 99%
“…Ingordo et al [7] confirmed a satisfactory repeatability with two different HDM extracts in eight patients with atopic dermatitis, 37 atopic patients without eczema and 19 atopic patients [7]. Ingordo et al [7] confirmed a satisfactory repeatability with two different HDM extracts in eight patients with atopic dermatitis, 37 atopic patients without eczema and 19 atopic patients [7].…”
Section: Reproducibilitymentioning
confidence: 92%
“…Ingordo et al [7] performed APTs with house dust mite (HDM) extracts (extract of purified bodies of HDM at 20% and with another extract of whole bodies of HDM at 30%, the latter corresponding to 300 mg/g Der p 1.) Ingordo et al [7] performed APTs with house dust mite (HDM) extracts (extract of purified bodies of HDM at 20% and with another extract of whole bodies of HDM at 30%, the latter corresponding to 300 mg/g Der p 1.)…”
Section: Sensitivity and Specificitymentioning
confidence: 99%